2020
DOI: 10.1108/reps-03-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency of health-care systems in selected middle-income countries: an empirical investigation

Abstract: Purpose This paper aims to evaluate the technical efficiency of the health-care systems in 21 selected middle-income countries during the period (2000–2017) and determine the source of inefficiency whether it is transient (short run) or persistent (long run). Design/methodology/approach The study uses the stochastic frontier analysis technique through employing the generalized true random effects model which overcomes the drawbacks of the previously introduced stochastic frontier models and allows for the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We synthesised the inputs and outputs under system-level studies and health facility/sub-national level studies. Out of the 12 system-level efficiency studies included, expenditure (n = 10) was the most used input variable [ 6 , 13 - 16 , 47 , 49 , 50 , 52 , 53 ], followed by total health workforce (n = 6) [ 6 , 13 , 47 , 48 , 51 , 52 ], and capacity (n = 3) [ 6 , 48 , 51 ]. Other input variables included unemployment rate [ 6 , 50 ], immunisation rate, Gini coefficient [ 50 , 53 ], educational index [ 49 , 50 ], age group of participants [ 14 , 50 ], food production index, inflation rate, purchasing power parity, urbanisation [ 49 ], external resources [ 14 ], and use of sanitation services [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…We synthesised the inputs and outputs under system-level studies and health facility/sub-national level studies. Out of the 12 system-level efficiency studies included, expenditure (n = 10) was the most used input variable [ 6 , 13 - 16 , 47 , 49 , 50 , 52 , 53 ], followed by total health workforce (n = 6) [ 6 , 13 , 47 , 48 , 51 , 52 ], and capacity (n = 3) [ 6 , 48 , 51 ]. Other input variables included unemployment rate [ 6 , 50 ], immunisation rate, Gini coefficient [ 50 , 53 ], educational index [ 49 , 50 ], age group of participants [ 14 , 50 ], food production index, inflation rate, purchasing power parity, urbanisation [ 49 ], external resources [ 14 ], and use of sanitation services [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been documented that between 20% and 40% of health system resources are not used appropriately. 30 Regarding technical efficiency of the HECP to achieve initiated communities, informed communities, and certified communities, only 4 or 5 states (out of 32) get the maximum frontier of production. 27 These results show the low levels of technical efficiency of the program.…”
Section: Discussionmentioning
confidence: 99%
“…Efficiency is a relevant issue because public resources to finance programs are scarce. It has been documented that between 20% and 40% of health system resources are not used appropriately 30. Regarding technical efficiency of the HECP to achieve initiated communities, informed communities, and certified communities, only 4 or 5 states (out of 32) get the maximum frontier of production 27.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that decentralisation of health functions was associated with higher technical efficiency of national and subnational health systems [59]. An assessment of the technical efficiency of healthcare systems of selected middle-income countries found that technical efficiency was enhanced by decentralisation, which enhanced the delivery of care in rural areas, and improved the responsiveness of health systems to community needs through improved community participation in healthcare decision making [104]. Effective performance monitoring and accountability was found to improve health system efficiency in Canada [46].…”
Section: Health System Characteristicsmentioning
confidence: 99%